2020
DOI: 10.21203/rs.3.rs-17219/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a patient-reported outcome questionnaire for aplastic anemia and paroxysmal nocturnal hemoglobinuria (PRO-AA/PNH)

Abstract: Background: The introduction of new therapy modalities has significantly improved the outcome of aplastic anemia (AA) and paroxysmal nocturnal hemoglobinuria (PNH) patients. However, relatively little is known about the exact disease burden of AA/PNH since standardized assessments of symptoms including health-related quality of life (HRQoL) are frequently missing or inadequately designed for this rare patient group. We aimed to develop AA/PNH-specific questionnaires for self-reporting of symptoms, which could … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Although this feasibility study was not designed to assess the frequency of reported symptoms of AA/PNH patients, and therefore these results should be interpreted with caution, we still can make out interesting observations. Using our recently developed PRO questionnaire (26) it was possible to detect less known symptoms in this disease entity (e.g. concentration problems), which could point towards an underestimation of these symptoms in AA/PNH and opens a window for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this feasibility study was not designed to assess the frequency of reported symptoms of AA/PNH patients, and therefore these results should be interpreted with caution, we still can make out interesting observations. Using our recently developed PRO questionnaire (26) it was possible to detect less known symptoms in this disease entity (e.g. concentration problems), which could point towards an underestimation of these symptoms in AA/PNH and opens a window for future research.…”
Section: Discussionmentioning
confidence: 99%
“…The ePRO system incorporated a prede ned algorithm to stratify patient-reported symptoms in real-time into minor, moderate and severe symptoms (26), each resulting in different actions (Tables 1 and 4, Fig. 4): In case of minor or moderate symptoms, patients would automatically receive selfmanagement advice.…”
Section: Clinical Test Phasementioning
confidence: 99%